In vitro Exposure to Inflammatory Mediators Affects the Differentiation of Mesenchymal Progenitors - Marsh, S.; Constantin-Teodosiu, T.; Chapman, V.; Sottile, V. (Frontiers in Bioengineering and Biotechnology, 2022)
The increasing prevalence of joint disease, and in particular osteoarthritis (OA), calls for novel treatment strategies to prevent disease progression in addition to existing approaches focusing mainly on the relief of pain symptoms. The inherent properties of mesenchymal stem cells (MSCs) make them an attractive candidate for novel tissue repair strategies, as these progenitors have the potential to differentiate into chondrocytes needed to replace degraded cartilage and can exert a modulating effect on the inflammatory environment of the diseased joint. However, the inflammatory environment of the joint may affect the ability of these cells to functionally integrate into the host tissue and exert beneficial effects, as hinted by a lack of success seen in clinical trials. Identification of factors and cell signalling pathways that influence MSC function is therefore critical for ensuring their success in the clinic, and here the effects of inflammatory mediators on bone marrow-derived MSCs were evaluated. Human MSCs were cultured in the presence of inflammatory mediators typically associated with OA pathology (IL-1β, IL-8, IL-10). While exposure to these factors did not produce marked effects on MSC proliferation, changes were observed when the mediators were added under differentiating conditions. Results collected over 21 days showed that exposure to IL-1β significantly affected the differentiation response of these cells exposed to chondrogenic and osteogenic conditions, with gene expression analysis indicating changes in MAPK, Wnt and TLR signalling pathways, alongside an increased expression of pro-inflammatory cytokines and cartilage degrading enzymes. These results highlight the value of MSCs as a preclinical model to study OA and provide a basis to define the impact of factors driving OA pathology on the therapeutic potential of MSCs for novel OA treatments.